A study on factors affecting frequency of absenteeism among students in UiTM Alor Gajah campus Melaka / Nasir Nordin , Rozalli Hashim , Azizah Dolah , Asmah Zainuddin , Aida Azlina Mohd Bee - Nordin, Nasir; Hashim, Rozalli; Dolah, Azizah; Zainuddin, Asmah; Mohd Bee, Aida Azlina (Institute of Research, Development and Commercialization , Universiti Teknologi MARA, 2002)
This study looks at factors that influence student frequency of absenteeism in a university setting. Twenty variables categorized into nine groups are examined, namely; gender, commuting, timetable, courses attended, assignments and tests, extra-curricular activities, health, social influence and academic performance. Most of the variables are significant to frequency of absenteeism. The empirical results indicate that absenteeism is a phenomenon that is controllable through sound policies and support system. The result also shows that besides students' own attitude, the administration, lecturers, family and the community have important roles to play in order to encourage students to classes. While disciplinary measures are still relevant, proactive intervention by lecturers and administrators can reduce the rate of class absenteeism.